OC18: Transspinal direct current stimulation for pain treatment. Objective proof of concept, initial clinical findings and BDNF polymorphism. (March 2022) - Thordstein, M.; Rahin, H.E.D.A.Y.; Jackson, W.
Abstract : Introduction Transspinal Direct Current Stimulation (tsDCS) has been reported to block pain signaling. To approach clinical usage, two studies were performed. In both, the effect of BDNF polymorphism (Val/Met) was investigated. Materials and methods Study I Nineteen healthy controls, the anode over the tenth thoracic vertebra, the cathode over the shoulder. tsDCS: 2.5 A for 20 minutes, double blinded cross over design. Laser Evoked Potentials (LEPs): Stimulation of the dorsum of the hand and foot respectively, recordings at baseline, immediately after- and 30 minutes after the tsDCS stimulation. Amplitude and latency of the N2 peak was assessed and the subjects rated pain intensity. BDNF polymorphism was investigated in DNA from buccal mucosa cells. Study II Patients with neuropathic pain due to polyneuropathy are recruited. tsDCS is given at three days with one day between, BDNF polymorphism investigated as above. Results Study I Group level: LEP amplitudes successively reduced over time. Placebo; latencies unaffected from upper-, slightly increased from lower extremities. Verum; transiently increased from upper-, accumulatively increased from lower extremities in proportion to experienced pain. Individual level: Large variations. BDNF polymorphism influences the effect of stimulation with less pain reduction in those with less active BDNF (Val/Val). Study II Fourteen patients have been investigated. The results will be presented at the conference. Conclusions Short term, anodal thoracic tsDCS affects transspinal pain signaling with large inter-individual differences. Individualized tsDCS may be a treatment option for neuropathic pain. The type of BDNF one carries, seem to influence the effect of stimulation.